Perencanaan Perbaikan Infrastruktur Jalan Oleh Pemerintah Kota Pekanbaru Tahun 2023 - Fadhiilatun Nisaa; Adlin Adlin; Ben Hansel Notatema Zebua (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2023)
Riau Province is the second province with the most damaged roads in Indonesia (based on BPS 2022 data), reaching 633km. Pekanbaru City as the provincial capital certainly has important main roads. Of the 1,277km of roads in Pekanbaru City, there are 400km of damaged roads. In 2023, the Pekanbaru government plans and carries out a road repair program in the form of overlaying. The purpose of this study is to describe how the Pekanbaru City Government is planning to improve road infrastructure in 2023. Using qualitative research methods and for data collection, researchers used library research. The approach used uses the concept of government management (planning). The results of this study are that the Pekanbaru city government has implemented good government management, through planning road repairs with patchwork and overlays with clear and timely targets and targets. However, monitoring, evaluation and supervision mechanisms are needed in carrying out planning for damaged road repairs in Pekanbaru City.